Gonomyia (Gonomyia) lucidula de Meijere and allies (Diptera: Limoniidae) - Starý, Jaroslaw (Entomologica Fennica, 2011)
Gonomyia (Gonomyia) lucidula de Meijere, 1920 and G. (G.) abscondita Lackschewitz, 1935 are redescribed, and the lectotypes of both species are designated. Desciptions of another two species are provided, viz. G. (G.) securiformis sp. n. (Bulgaria, Czech Republic, Italy, Switzerland) and G. (G.) undiformis sp. n. (Slovakia). Male terminalia are illustrated and distributions are outlined for all the species.